Lithium secondary battery, battery module, and battery pack

Optimizing nickel, cobalt, and manganese-based lithium composite transition metal compounds with silicon carbon composites addresses the limitations of lithium cobalt oxide and non-carbon negative electrodes, enhancing energy density and cycle life in lithium secondary batteries for diverse applications.

JP2025501771AActive Publication Date: 2025-01-23LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024538447
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2023-07-20
Publication Date
2025-01-23
Estimated Expiration
2043-07-20

Smart Images

  • Figure 2025501771000001
    Figure 2025501771000001
  • Figure 2025501771000002
    Figure 2025501771000002
  • Figure 2025501771000003
    Figure 2025501771000003
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery. In one embodiment, the lithium secondary battery includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, a separator provided between the positive electrode and the negative electrode, and an electrolyte, the positive electrode active material includes a lithium composite transition metal compound including nickel, cobalt, and manganese, the lithium composite transition metal compound includes at least one of single particles or similar-single particles, the average particle size of at least one of the single particles or similar-single particles is 1 μm or more, the single particle is composed of one node, and the similar-single particle is a complex consisting of 30 nodes or less, the negative electrode active material includes a silicon carbon composite, the average particle size of the silicon carbon composite is more than 1 μm, and the average particle size of at least one of the single particles or similar-single particles is smaller than the average particle size of the silicon carbon composite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0097491 filed with the Korean Intellectual Property Office on August 4, 2022 and the benefit of the filing date of Korean Patent Application No. 10-2023-0091528 filed with the Korean Intellectual Property Office on July 14, 2023, and all contents disclosed in the documents of the Korean patent application are incorporated herein by reference.

[0002] The present application relates to a lithium secondary battery, a battery module, and a battery pack. [Background technology]

[0003] In recent years, with the rapid spread of battery-powered electronic devices such as mobile phones, laptops, and electric vehicles as well as power tools and vacuum cleaners, the demand for secondary batteries that are small and lightweight yet have relatively high capacity and / or high output is rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for electronic devices. As a result, research and development efforts are being actively conducted to improve the performance of lithium secondary batteries.

[0004] In a lithium secondary battery, an organic electrolyte or polymer electrolyte is filled between a positive electrode and a negative electrode, which are made of active materials that allow the intercalation and deintercalation of lithium ions, and electrical energy is produced by oxidation and reduction reactions that occur when lithium ions are inserted and extracted from the positive and negative electrodes.

[0005] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4), etc. are used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used because of its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price of cobalt (Co) and unstable supply, there is a limit to its mass use as a power source in fields such as electric vehicles, and the need for the development of an alternative positive electrode active material has emerged.

[0006] As a result, nickel-cobalt-manganese-based lithium transition metal composite compounds (hereinafter simply referred to as "NCM-based lithium transition metal composite compounds") were developed in which part of the cobalt (Co) was replaced with nickel (Ni) and manganese (Mn). In recent years, research has been conducted to increase the Ni content in NCM-based lithium transition metal composite compounds to increase capacity. However, high-concentration nickel (Ni-rich) positive electrode active materials with a high nickel content have the disadvantages of reduced thermal stability and increased resistance and gas generation due to increased side reactions during electrochemical reactions.

[0007] On the other hand, graphite is mainly used as the negative electrode active material for lithium secondary batteries, but since graphite has a small capacity per unit mass of 372 mAh / g, it is difficult to increase the capacity of lithium secondary batteries. For this reason, in order to increase the capacity of lithium secondary batteries, negative electrode materials such as silicon, tin, and their oxides have been developed as non-carbon-based negative electrode materials with higher energy density than graphite. However, such non-carbon-based negative electrode materials have problems such as low initial efficiency, large lithium consumption during initial charging and discharging, and large irreversible capacity loss, although they have a large capacity. Summary of the Invention [Problem to be solved by the invention]

[0008] The present inventors have discovered that in a lithium secondary battery designed within a limited space, optimal battery performance can be achieved by a specific combination of the type, average particle size, and / or content of each component of the active materials constituting the positive and negative electrodes, and have completed the present invention. [Means for solving the problem]

[0009] According to an embodiment of the present application, there is provided a lithium secondary battery including a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator provided between the positive electrode and the negative electrode; and an electrolyte, in which the positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), the lithium transition metal composite compound includes at least one of a single particle or a similar-single particle, and at least one of the single particle or the similar-single particle has an average particle diameter (D50) of 1 μm or more, the single particle is composed of one node, and the similar-single particle is a composite having 30 nodes or less, and the negative electrode active material includes a silicon carbon composite, and the average particle diameter (D50) of the silicon carbon composite exceeds 1 μm, and the average particle diameter (D50) of at least one of the single particle or the similar-single particle is smaller than the average particle diameter (D50) of the silicon carbon composite. A battery module and a battery pack including the lithium secondary battery are provided. Effect of the Invention

[0010] According to the embodiments described herein, it is possible to increase the energy density of a lithium secondary battery designed in a limited space, improve the high-output performance, and also improve the cycle performance of the battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in more detail below to help understanding of the present invention. The present invention may be realized in various different forms and is not limited to the embodiments described herein. In this regard, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as meanings and concepts that are consistent with the technical ideas of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0012] It should be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0013] In addition, when a part such as a layer is said to exist "on" or "above" another part, this includes not only the case where it exists "directly above" the other part, but also the case where there is another part between them. Conversely, when a part is said to exist "directly above" another part, it means that there is no other part between them. In addition, being "on" or "above" a reference part means being located above or below the reference part, and does not necessarily mean being located "on" or "above" the reference part in the opposite direction of gravity.

[0014] In the present specification, "and / or" refers to the selection of one of the listed items, and "and" refers to all of the listed items. For example, "A and / or B" refers to both the case of "A and B" and the case of "A or B."

[0015] In this specification, the term "single particle" may mean a particle consisting of a single nodule. The "nodule" may be a single crystal without grain boundaries, or may be a polycrystal in which grain boundaries are not apparent when observed at 5000 to 20000 magnifications using a scanning electron microscope (SEM). In this specification, the term "quasi-single particle" may mean an aggregate consisting of 30 or less nodules. In this specification, the term "secondary particle" means a particle formed by agglomeration of tens to hundreds of primary particles, and specifically, the secondary particle may include a particle formed by agglomeration of 50 or more primary particles.

[0016] As used herein, "particle" may include at least one of a single particle, a quasi-single particle, a primary particle, a nodule, and a secondary particle.

[0017] In this specification, the "average particle size (D50)" can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve of the particles. The average particle size (D50) can be measured, for example, by using a laser diffraction method. The laser diffraction method can generally measure particle sizes from the submicron range to several mm, and can obtain results with high reproducibility and high resolution.

[0018] The average particle size (D50) can be measured using a Microtrac device (manufacturer: Microtrac, model name: S3500) with water and triton-X100 dispersant. Specifically, the average particle size (D50) of the positive electrode active material can be measured at a refractive index of 1.5 to 1.7, and the average particle size (D50) of the negative electrode active material can be measured at a refractive index of 1.97 or 2.42. For example, the particles can be dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device, irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and then a volume cumulative particle size distribution graph can be obtained, and the particle size corresponding to 50% of the volume cumulative amount can be measured.

[0019] One embodiment of the present application provides a lithium secondary battery including: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator provided between the positive electrode and the negative electrode; and an electrolyte, in which the positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), the lithium transition metal composite compound includes single particles and / or similar-single particles, the single particles and / or similar-single particles have an average particle size (D50) of 1 μm or more, the single particle is composed of one node, and the similar-single particles are a complex consisting of 30 nodes or less, the negative electrode active material includes a silicon carbon composite, the average particle size (D50) of the silicon carbon composite is more than 1 μm, and the average particle size (D50) of the single particles and / or similar-single particles is smaller than the average particle size (D50) of the silicon carbon composite.

[0020] The silicon carbon composite may be a Si / C based active material.

[0021] In this specification, the silicon carbon composite is a composite of Si and C, and is distinguished from silicon carbide, which is represented as SiC. Since silicon carbide does not electrochemically react with lithium, all performances, including lifespan, can be measured as zero.

[0022] The silicon carbon composite may be a composite of silicon and graphite, or may have a structure in which a core of silicon and graphite is surrounded by graphene or amorphous carbon. In the silicon carbon composite, the silicon may be nanosilicon. For example, the nanosilicon may be silicon in the range of 1 nm to 999 nm.

[0023] Lithium secondary batteries have a size required depending on the application, and therefore must be designed within a limited space. Consumer demands for increased energy density and improved high output performance are increasing, but when using a high-capacity positive electrode material, the content of the negative electrode material must be increased to match it, so there is a limit to how much battery efficiency can be increased within a limited space. In addition, it is necessary to design a positive electrode material with an efficiency that matches the efficiency of the negative electrode material depending on the type of negative electrode material.

[0024] For example, the energy density can be improved, but if the porosity of the positive electrode is reduced to increase the electrode density, strong rolling for this purpose can cause cracks in the particles, which can lead to a decrease in battery performance.

[0025] The single particles used in the embodiments of the present application have high rigidity and are relatively less susceptible to deterioration in battery performance even when the electrode density is high. Therefore, the energy density can be increased by combining the single particles and the silicon carbon composite according to the above average particle size range.

[0026] According to a further embodiment of the present application, the positive electrode active material comprises a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), the lithium transition metal composite compound comprising single particles and / or similar-single particles, and the single particles and / or similar-single particles have an average particle size (D50) of 1 μm or more.

[0027] As the average particle diameter (D50) of the single particles becomes smaller, the specific surface area increases, which may increase side reactions with the electrolyte and reduce electrochemical performance such as lifespan. If the average particle diameter (D50) of the single particles is less than 1 μm, this is not within the range of commercial application, and even if it does exist, it may be difficult to apply it because the lifespan performance is very low due to the increase in the specific surface area.

[0028] When the average particle size (D50) of the single particle is 1 μm or more, 3 μm or more, or 5 μm or more, the single particle reduces side reactions with the electrolyte and has excellent life performance.

[0029] In addition, the negative active material includes a silicon carbon composite, the silicon carbon composite has an average particle size (D50) of more than 1 μm, and the average particle size (D50) of the single particle and / or quasi-single particle is smaller than the average particle size (D50) of the silicon carbon composite.

[0030] As the average particle size (D50) of the silicon carbon composite decreases, the specific surface area increases, which increases side reactions with the electrolyte, and electrochemical performance such as lifespan may decrease. If the average particle size (D50) of the silicon carbon composite is less than 1 μm, the side reactions increase due to the increase in specific surface area, and lifespan performance is very low, making it difficult to apply the composite.

[0031] When the average particle size (D50) of the silicon carbon composite is more than 1 μm, more than 3 μm, more than 5 μm, or more than 5 μm, side reactions with the electrolyte are reduced, resulting in excellent life performance.

[0032] The silicon carbon composite has excellent life performance within the above range, and the Si crystal grain size of the silicon carbon composite may be 10 nm or less. The silicon carbon composite has excellent initial capacity and efficiency compared to other silicon-based materials such as SiO, and also has excellent electrochemical performance, and can achieve optimal battery performance by combining the average grain size with the single particle.

[0033] The single particles and / or quasi-single particles may have excellent particle strength even when formed into a small particle size, thereby mitigating the phenomenon of an increase in fine particles in the electrode due to particle cracking, thereby improving the life characteristics of the battery.

[0034] When the average particle size (D50) of the single particle and / or similar-single particle is smaller than the average particle size (D50) of the silicon carbon composite, the diffusion resistance of the single particle and / or similar-single particle is relatively decreased, and the life performance can be improved. That is, lithium enters the single particle and / or similar-single particle on a discharge basis, and the diffusion resistance can be increased as the average particle size (D50) of the single particle and / or similar-single particle is larger. When the average particle size (D50) of the single particle and / or similar-single particle is larger than the average particle size (D50) of the silicon carbon composite, the diffusion resistance is relatively increased, and lithium precipitates without entering the single particle and / or similar-single particle, which can deteriorate the battery performance and deteriorate the life performance.

[0035] In addition, when the average particle size (D50) of the single particle is smaller than the average particle size (D50) of the silicon carbon composite, side reactions with the electrolyte due to an increase in the specific surface area of ​​the single particle can be prevented, and life performance can be improved.

[0036] When the average particle size (D50) of the single particle and / or similar-single particle is smaller than the average particle size (D50) of the silicon carbon composite, the diffusion resistance of the single particle and / or similar-single particle is relatively reduced, and the life performance can be improved.

[0037] Since the single particle and / or similar-single particle have a higher lithium diffusion resistance than the silicon carbon composite, if the average particle diameter (D50) of the single particle and / or similar-single particle is larger than the average particle diameter (D50) of the silicon composite, the increase in lithium diffusion resistance may result in insufficient charge / discharge, resulting in a decrease in life performance. Therefore, the average particle diameter (D50) of the single particle and / or similar-single particle may be smaller than the average particle diameter (D50) of the silicon carbon composite.

[0038] According to a further embodiment of the present application, the positive electrode active material includes nickel, cobalt, and manganese, and may further include aluminum.

[0039] In this specification, the positive electrode active material contains 80 mol % or more and less than 100 mol % of nickel among metals excluding lithium, and the lithium transition metal compound containing 80 mol % or more and less than 100 mol % of nickel among metals excluding lithium may include one or a mixture of two or more types represented by the following chemical formula 1.

[0040] The lithium composite transition metal compound may also include single particles and / or similar-single particles and secondary particles.

[0041] [Chemical formula 1] Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ

[0042] In the above formula, Q is at least one element selected from the group consisting of Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr, and 1≦a≦1.5, 0 <b≦0.5、0<c≦0.5、0≦d≦0.1、0<b+c+d≦20、-0.1≦δ≦1.0である。

[0043] In the lithium transition metal composite compound of Formula 1, Li may be included in an amount corresponding to a, i.e., 1≦a≦1.5. If a is less than 1, the capacity may decrease, and if it exceeds 1.5, the particles may be sintered during the firing process, making it difficult to prepare the positive electrode active material. In consideration of the effect of improving the capacity characteristics of the positive electrode active material by controlling the Li content and the balance between sinterability during the preparation of the active material, the Li may be included in an amount of 1.1≦a≦1.2, more preferably.

[0044] In the lithium composite transition metal compound of Chemical Formula 1, Ni may be contained in an amount corresponding to 1-(b + c + d), for example, 0.8 ≦ 1-(b + c + d) < 1. If the content of Ni in the lithium composite transition metal compound of Chemical Formula 1 is 0.8 or more, a sufficient amount of Ni for contributing to charge and discharge is ensured, and high capacity can be achieved. Preferably, 1-(b + c + d), which is the content of Ni, may be 0.88, preferably 0.9 or more, more preferably 0.93 or more. Preferably, 1-(b + c + d), which is the content of Ni, may be 0.99 or less, 0.95 or less.

[0045] In the lithium composite transition metal compound of Chemical Formula 1, Co may be contained in an amount corresponding to b, that is, 0 < b ≦ 0.5. If the content of Co in the lithium composite transition metal compound of Chemical Formula 1 exceeds 0.5, there is a risk of increased cost. Considering the remarkable effect of improving the capacity characteristics by including Co, more specifically, Co may be contained in an amount of 0.03 ≦ b ≦ 0.2.

[0046] In the lithium composite transition metal compound of Chemical Formula 1, Mn may be contained in an amount corresponding to c, that is, 0 < c ≦ 0.5. If c in the lithium composite transition metal compound of Chemical Formula 1 exceeds 0.5, there is a risk that the output characteristics and capacity characteristics of the battery may instead deteriorate. More specifically, Mn may be contained in an amount of 0.01 ≦ c ≦ 0.2.

[0047] In the lithium composite transition metal compound of Chemical Formula 1, Q may be a doping element contained in the crystal structure of the lithium composite transition metal compound, and Q may be contained in an amount corresponding to d, that is, 0 ≦ d ≦ 0.1. Q may be one or more selected from Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr. For example, Q may be Al.

[0048] According to a further embodiment of the present application, the lithium transition metal composite compound in the positive electrode active material may include single particles and / or similar-single particles and secondary particles.

[0049] The single particles and / or the similar-single particles can be produced by mixing a transition metal precursor and a lithium source material and sintering the mixture. The secondary particles may be produced by a method different from that of the single particles and / or the similar-single particles, and the composition of the secondary particles may be the same as or different from that of the single particles and / or the similar-single particles.

[0050] For example, the firing is performed at a temperature at which single particles and / or similar-single particles can be formed. To form them, firing should be performed at a higher temperature than that at which secondary particles are produced. For example, when the precursor composition is the same, firing should be performed at a temperature about 30°C to 100°C higher than that at which secondary particles are produced. The firing temperature for forming the single particles and / or similar-single particles may vary depending on the composition of the metal in the precursor. For example, when a high-content nickel (High-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol% or more is to be formed into single particles and / or similar-single particles, the firing temperature may be about 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive electrode active material containing single particles and / or similar-single particles having excellent electrochemical properties can be produced. If the calcination temperature is less than 790°C, a positive electrode active material containing a lithium transition metal composite compound in the form of secondary particles may be produced, whereas if the calcination temperature exceeds 950°C, excessive calcination may occur, resulting in insufficient formation of a layered crystal structure and reduced electrochemical properties.

[0051] In this specification, the terms "single particle" and / or "quasi-single particle" are used to distinguish them from conventional secondary particles formed by agglomeration of tens to hundreds of primary particles.

[0052] Specifically, in the present invention, a single particle is composed of one node, and the similar-single particle is a complex composed of 30 or less nodes, whereas a secondary particle may be in the form of an aggregate of several hundred primary particles.

[0053] According to a further embodiment of the present application, the average particle size (D50) of said monoparticles and / or quasi-monoparticles is equal to or greater than 1 μm and the average particle size (D50) of said silicon carbon composite is greater than 1 μm.

[0054] The monoparticulate and / or quasi-monoparticulate may have an average particle size (D50) of more than 1 μm, and the silicon carbon composite may have an average particle size (D50) of more than 1 μm.

[0055] According to an embodiment of the present application, the average particle size (D50) of the monoparticles and / or quasi-monoparticles is less than or equal to 12 μm, and the average particle size (D50) of the silicon carbon composite is less than 15 μm.

[0056] For example, the average particle size (D50) of the monoparticles and / or similar-monoparticles may be 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 5 μm or less, more than 1 μm and 12 μm or less, more than 1 μm and 8 μm or less, or more than 1 μm and 5 μm or less.

[0057] Even if the average particle size (D50) of the single particle and / or the quasi-single particle is small, such as 1 μm to 12 μm, the particle strength can be excellent. For example, the single particle and / or the quasi-single particle has a strength of 650 kgf / cm 2 When the rolling force is 650 kgf / cm, the particle strength of the single particle and / or the quasi-single particle can be 100 MPa to 300 MPa. 2 Even if the electrode is rolled with a strong force, the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, thereby improving the life characteristics of the battery.

[0058] When the average particle diameter (D50) of the single particle satisfies the above range, the single particle reduces side reactions with the electrolyte, has excellent life performance, is sufficiently charged / discharged, and has excellent electrochemical performance.

[0059] When the average particle diameter (D50) of the single particles is less than 1 μm, the life performance is very low due to the increase in specific surface area, so that it may be difficult to apply the same.

[0060] When the average particle size (D50) of the single particles is 12 μm or less, charging / discharging is performed sufficiently and the electrochemical performance is excellent.

[0061] The method for forming the single particles and / or quasi-single particles is not particularly limited, but may generally be formed by over-firing at an elevated firing temperature, using additives such as grain growth promoters that aid in over-firing, or by changing the starting material.

[0062] According to a further embodiment of the present application, the silicon carbon composite may have an average particle size (D50) of more than 1 μm and less than 15 μm, 2 μm or more and 14 μm or less, or 3 μm or more and 13 μm or less.

[0063] Even if the silicon carbon composite has a small average particle size (D50) of more than 1 μm and less than 15 μm, the lifespan characteristics of the battery can be improved. For example, when the silicon carbon composite has an average particle size (D50) in the range of more than 1 μm and less than 15 μm, the rate of volume expansion and contraction due to charging and discharging is reduced, and lifespan performance can be improved. In addition, an excessive increase in specific surface area is prevented, and side reactions with the electrolyte due to cycle progression are not caused, and lifespan performance can be improved.

[0064] When the average particle size (D50) of the silicon carbon composite is less than 1 μm, the life performance is very low due to the increase in specific surface area, so that it may be difficult to apply the composite.

[0065] When the average particle size (D50) of the silicon carbon composite is less than 15 μm, the particles are small, charging and discharging are performed sufficiently, and the volume expansion and contraction rate of the particles due to charging and discharging is reduced, thereby improving the life performance.

[0066] According to a further embodiment of the present application, the average particle size (D50) of the single particle and / or the quasi-single particle is smaller than the average particle size (D50) of the silicon carbon composite. As a result, the single particle and / or the quasi-single particle can have excellent particle strength even when formed to have a small particle size, and thus the increase in fine particles in the electrode due to particle cracking can be mitigated, thereby improving the life characteristics of the battery.

[0067] When the average particle size (D50) of the single particle and / or similar-single particle is smaller than the average particle size (D50) of the silicon carbon composite, the lithium diffusion resistance of the single particle and / or similar-single particle, which has a higher lithium diffusion resistance than the silicon carbon composite, is relatively reduced, and the life performance can be improved.

[0068] According to one embodiment of the present application, the average particle size (D50) of the monoparticles and / or quasi-monoparticles may be 1 μm to 12 μm smaller than the average particle size (D50) of the silicon carbon composite.

[0069] The average particle size (D50) of the monoparticles and / or quasi-monoparticles may be smaller than the average particle size (D50) of the silicon carbon composite by 1.5 μm to 11.5 μm, or 2 μm to 11 μm.

[0070] The average particle size (D50) of the monoparticulates and / or quasi-monoparticulates may be 2 μm or more, or 4 μm or more smaller than the average particle size (D50) of the silicon carbon composite. The average particle size (D50) of the monoparticulates may be 11 μm or less, 8 μm or less, or 6 μm or less smaller than the average particle size (D50) of the silicon carbon composite.

[0071] When the average particle size (D50) of the single particle and / or similar-single particle is smaller than the average particle size (D50) of the silicon carbon composite, for example, when the above range is satisfied, the diffusion resistance of the single particle and / or similar-single particle is relatively decreased, and the life performance can be improved. That is, the larger the average particle size (D50) of the single particle and / or similar-single particle, the higher the diffusion resistance can be. When the average particle size (D50) of the single particle and / or similar-single particle is larger than the average particle size (D50) of the silicon carbon composite, the diffusion resistance is relatively increased, which may cause lithium precipitation, degrade battery performance, and degrade life performance.

[0072] In addition, when the average particle size (D50) of the monoparticles and / or quasi-monoparticles is smaller than the average particle size (D50) of the silicon carbon composite, for example, when the average particle size (D50) satisfies the above range, side reactions with the electrolyte due to an increase in specific surface area can be prevented, and life performance can be improved.

[0073] According to one embodiment of the present application, the ratio of the average particle size (D50) of the single particles and / or quasi-single particles to the average particle size (D50) of the silicon carbon composite is 1.5:2 to 1.5:20.

[0074] The ratio of the average particle size (D50) of the single particles to the average particle size (D50) of the silicon carbon composite may be 1.5:2 to 1.5:19, or 1.5:2 to 1.5:18.

[0075] The ratio of the average particle size (D50) of the single particles to the average particle size (D50) of the silicon carbon composite may be 1.5:2 or more, 1.5:2.5 or more, 1.5:3.5 or more, or 1.5:4.5 or more. The ratio of the average particle size (D50) of the single particles to the average particle size (D50) of the silicon carbon composite may be 1.5:18 or less, 1.5:16 or less, 1.5:14 or less, 1.5:12 or less, or 1.5:10 or less.

[0076] When the above range is satisfied, the diffusion resistance of the single particles and / or similar-single particles is relatively decreased, and the life performance can be improved. That is, the larger the average particle diameter (D50) of the single particles and / or similar-single particles, the higher the diffusion resistance can be. When the average particle diameter (D50) of the single particles and / or similar-single particles is larger than the average particle diameter (D50) of the silicon carbon composite, the diffusion resistance increases relatively, and thus lithium precipitation occurs, which can deteriorate the battery performance and life performance.

[0077] In addition, when the average particle size (D50) of the monoparticles and / or quasi-monoparticles is smaller than the average particle size (D50) of the silicon carbon composite, for example, when the average particle size (D50) satisfies the above range, side reactions with the electrolyte due to an increase in specific surface area can be prevented, and life performance can be improved.

[0078] In one embodiment of the present application, the lithium composite transition metal compound further includes secondary particles, and the average particle size (D50) of the single particle and / or the similar-single particle may be smaller than the average particle size (D50) of the secondary particles.

[0079] In the present invention, a monoparticle consists of one nodule, and a similar monoparticle may be in the form of a complex consisting of up to 30 nodules.

[0080] The lithium transition metal composite compound may further include secondary particles. The secondary particles refer to a form formed by agglomeration of primary particles, and are distinguished from the concept of a similar-single particle, which is a single particle consisting of one node or an aggregate consisting of 30 or less nodes.

[0081] The particle diameter (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles is 0.05 m 2 / g~10m 2 / g, preferably 0.1m 2 / g~1m 2 / g, more preferably 0.3m 2 / g~0.8m 2 / g.

[0082] In a further embodiment of the present application, the secondary particles may be aggregates of primary particles, and the primary particles may have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of several hundred primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.

[0083] When the average particle size (D50) of the aggregated primary particles in the secondary particles satisfies the above range, a single particle and / or similar-single particle positive electrode active material having excellent electrochemical properties can be formed. When the average particle size (D50) of the aggregated primary particles in the secondary particles is too small, the number of aggregates of the primary particles forming the lithium nickel-based oxide particles increases, and the effect of suppressing particle cracking during rolling decreases. When the average particle size (D50) of the aggregated primary particles in the secondary particles is too large, the lithium diffusion path inside the primary particles becomes longer, increasing resistance and causing a decrease in output characteristics.

[0084] According to a further embodiment of the present application, the average particle size (D50) of the single particles and / or the quasi-single particles is smaller than the average particle size (D50) of the secondary particles. As a result, the single particles and / or the quasi-single particles can have excellent particle strength even when formed to have a small particle size, and thus the increase in fine particles in the electrode due to particle cracking can be mitigated, thereby improving the life characteristics of the battery.

[0085] In one embodiment of the present application, the average particle size (D50) of the single particles and / or quasi-single particles may be smaller than the average particle size (D50) of the secondary particles by 1 μm to 18 μm.

[0086] For example, the average particle size (D50) of the single particles and / or quasi-single particles may be 1 μm to 16 μm smaller, 1.5 μm to 15 μm smaller, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.

[0087] The average particle size (D50) of the monoparticulates and / or quasi-monoparticulates may be 1 μm or more, 2 μm or more, 4 μm or more, or 6 μm or more smaller than the average particle size (D50) of the secondary particles. The average particle size (D50) of the monoparticulates and / or quasi-monoparticulates may be 18 μm or less, 16 μm or less, 14 μm or less, 12 μm or less, 10 μm or less, or 8 μm or less smaller than the average particle size (D50) of the secondary particles.

[0088] When the average particle size (D50) of the single particles and / or the quasi-single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above range is satisfied, the single particles and / or the quasi-single particles can have excellent particle strength even if they are formed to have a small particle size, and thus the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, thereby improving the life characteristics and energy density of the battery.

[0089] In one embodiment of the present application, the negative electrode active material may further include graphite, and an average particle size (D50) of the silicon carbon composite may be smaller than an average particle size (D50) of the graphite.

[0090] When the average particle size (D50) of the silicon carbon composite is smaller than the average particle size (D50) of the graphite, the volume expansion / contraction rate during charging / discharging is reduced, thereby reducing particle cracking, and improving the battery life performance.

[0091] According to one embodiment of the present application, the average particle size (D50) of the silicon carbon composite is smaller than the average particle size (D50) of the graphite by 1 μm to 25 μm.

[0092] For example, the average particle size (D50) of the silicon-carbon composite may be 2 μm to 24 μm smaller than the average particle size (D50) of the graphite, may be 3 μm to 23 μm smaller, or may be 4 μm to 22 μm smaller.

[0093] The average particle size (D50) of the silicon-carbon composite may be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, or 10 μm or more smaller than the average particle size (D50) of the graphite. The average particle size (D50) of the silicon-carbon composite may be 25 μm or less, 23 μm or less, 22 μm or less, 20 μm or less, 18 μm or less, 16 μm or less, or 14 μm or less smaller than the average particle size (D50) of the graphite.

[0094] When the average particle size (D50) of the silicon-carbon composite is smaller than the average particle size (D50) of the graphite, for example, when the above range is satisfied, there is an effect that the life performance of the battery is improved.

[0095] In one embodiment of the present application, the lithium composite transition metal compound further includes secondary particles, the negative electrode active material further includes graphite, and the average particle sizes (D50) of the secondary particles, the single particles and / or similar-single particles, the graphite, and the silicon-carbon composite are represented by A, B, C, and D, respectively, and B < D ≤ A < C.

[0096] The embodiments of the secondary particles, the single particles and / or similar-single particles, the graphite, and the silicon-carbon composite are as described above.

[0097] When the average particle sizes (D50) of the secondary particles, the single particles and / or similar-single particles, the graphite, and the silicon-carbon composite are A, B, C, and D, respectively, when B < D ≤ A < C, there is an effect that the life performance of the battery is improved.

[0098] According to one embodiment of the present application, the negative electrode active material further comprises graphite, and the average particle size (D50) of the single particle and / or the similar-single particle, the graphite, and the silicon carbon composite is represented by B, C, and D, respectively, and B <D<Cである。

[0099] The average particle size (D50) of the secondary particles, the single particles and / or similar-single particles, and the silicon carbon composite is represented by A, B, and D, respectively; <D≦Aであってもよい。

[0100] The average particle size (D50) of the secondary particles, the single particles and / or similar-single particles, and the graphite are represented by A, B, and C, respectively; <A<Cであってもよい。

[0101] The average particle diameter (D50) of the secondary particles, the graphite, and the silicon carbon composite is represented by A, C, and D, respectively, and D≦A <Cであってもよい。

[0102] When the above range is satisfied, the effect of improving the life performance of the battery is achieved.

[0103] In one embodiment of the present application, in the lithium secondary battery according to the above-described embodiment, the single particles and / or similar-single particles may be included in an amount of 15 parts by weight to 100 parts by weight based on 100 parts by weight of the positive electrode active material, and the silicon carbon composite may be included in an amount of 3 parts by weight to 30 parts by weight based on 100 parts by weight of the negative electrode active material.

[0104] According to a further embodiment of the present application, the single particles and / or similar-single particles may be included in an amount of 15 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The single particles and / or similar-single particles may be included in an amount of 20 parts by weight to 100 parts by weight, 30 parts by weight to 100 parts by weight, 40 parts by weight to 100 parts by weight, or 50 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0105] For example, the monoparticles and / or quasi-monoparticles may be included in an amount of 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, 45 parts by weight or more, or 50 parts by weight or more, based on 100 parts by weight of the positive electrode active material. The monoparticles and / or quasi-monoparticles may be included in an amount of 100 parts by weight or less, based on 100 parts by weight of the positive electrode active material.

[0106] When the single particles and / or similar-single particles are contained in the above range, excellent battery characteristics can be exhibited in combination with the above-mentioned negative electrode material. In particular, when the single particles and / or similar-single particles are 15 parts by weight or more, the increase in fine particles in the electrode due to particle cracking during rolling after the electrode is manufactured can be mitigated, thereby improving the life characteristics of the battery.

[0107] In one embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the secondary particles may be included in an amount of 0 parts by weight to 85 parts by weight, 0 parts by weight to 70 parts by weight, or 0 parts by weight to 50 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0108] The secondary particles may be 85 parts by weight or less, 80 parts by weight or less, 75 parts by weight or less, 70 parts by weight or less, 65 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, or 50 parts by weight or less, relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 0 parts by weight or more, or 20 parts by weight or more, relative to 100 parts by weight of the positive electrode active material.

[0109] When the above range is satisfied, the above-mentioned effects due to the presence of the single particle and / or similar-single particle positive electrode active material can be maximized. When the secondary particle positive electrode active material is included, the components thereof may be the same as or different from those exemplified as the single particle and / or similar-single particle positive electrode active material described above, and may refer to the form in which the single particles are aggregated.

[0110] In one embodiment of the present application, the positive electrode active material may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less, relative to 100 parts by weight of the positive electrode active material layer.

[0111] According to one embodiment of the present application, the positive electrode according to the above-mentioned embodiment may further include a positive electrode binder and a conductive material.

[0112] The positive electrode binder can improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material particles and the positive electrode current collector. Any positive electrode binder known in the art can be used, and non-limiting examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0113] The positive electrode binder may be included in an amount of 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.

[0114] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0115] Specifically, in one embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). The conductive material may be included in an amount of 0.1 to 2 parts by weight based on 100 parts by weight of the composition for positive electrode active material layer, for example, preferably 0.3 to 1.5 parts by weight, more preferably 0.5 to 1.2 parts by weight.

[0116] In this specification, the silicon carbon composite is a composite of Si and C, and it is considered that the peaks of Si and C (graphite) are observed in the XRD diffraction pattern, and the second phase, Si / C, is not formed. The silicon carbon composite is to be distinguished from silicon carbide insulator represented by SiC.

[0117] According to the above-mentioned embodiment of the present application, the negative electrode active material layer may include 3 parts by weight to 30 parts by weight of the silicon carbon composite with respect to 100 parts by weight of the total negative electrode active material. According to one example, the negative electrode active material layer may include 3 parts by weight to 20 parts by weight, or 3 parts by weight to 13 parts by weight, preferably 5 parts by weight to 10 parts by weight of the silicon carbon composite with respect to 100 parts by weight of the total negative electrode active material.

[0118] The negative electrode active material layer may include 3 parts by weight or more, 4 parts by weight or more, or 5 parts by weight or more of a silicon carbon composite based on 100 parts by weight of a total negative electrode active material. The negative electrode active material layer may include 30 parts by weight or less, 20 parts by weight or less, or 10 parts by weight or less of a silicon carbon composite based on 100 parts by weight of a total negative electrode active material.

[0119] By using the silicon carbon composite in such a range, excellent battery characteristics can be exhibited in combination with the above-mentioned positive electrode material. In particular, when the silicon carbon composite is contained in an amount of 3 parts by weight or more, the effect of using the silicon carbon composite can be sufficiently exhibited. In addition, since the silicon carbon composite has a high capacity compared to the SiOx-based active material, it is difficult to balance the capacity with the positive electrode active material when used in excess, and especially when the silicon carbon composite is contained in an amount of 30 parts by weight or less, it is possible to prevent expansion during charging and discharging and improve cycle characteristics.

[0120] The silicon carbon composite is a material having a higher capacity and a higher efficiency than silicon-based oxides, and even if it does not contain a conductive material, it can exhibit a superior effect in terms of resistance compared to a negative electrode containing a silicon-based oxide and a conductive material. In addition, the silicon carbon composite exhibits higher Si crystallinity than silicon-based oxides, and therefore exhibits superior effects during high-output evaluation.

[0121] According to a further embodiment of the present application, in the lithium secondary battery according to the above embodiment, the negative electrode active material may further include a carbon-based active material. Specifically, the carbon-based active material may be graphite. The graphite may be natural graphite, artificial graphite, or a mixture thereof. The graphite may be included in an amount of 70 parts by weight or more and 97 parts by weight or less based on 100 parts by weight of the total negative electrode active material included in the negative electrode active material layer.

[0122] The graphite may be included in an amount of 75 parts by weight or more, 80 parts by weight or more, or 85 parts by weight or more, based on 100 parts by weight of the total negative electrode active material. The graphite may be included in an amount of 95 parts by weight or less, 93 parts by weight or less, or 90 parts by weight or less, based on 100 parts by weight of the total negative electrode active material. When the graphite is a mixture of artificial graphite and natural graphite, the artificial graphite and natural graphite may be included in an amount of 90:10 parts by weight to 50:50 parts by weight, 85:15 parts by weight to 60:40 parts by weight, or 80:20 parts by weight to 65:35 parts by weight, based on 100 parts by weight of the graphite.

[0123] In one embodiment of the present application, the negative electrode active material may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less, relative to 100 parts by weight of the negative electrode active material layer.

[0124] According to a further embodiment of the present application, in the lithium secondary battery according to the above-mentioned embodiment, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon carbon composite and graphite.

[0125] The negative electrode binder may improve adhesion between negative electrode active material particles and between the negative electrode active material particles and a negative electrode current collector. The negative electrode binder may be any material known in the art. Non-limiting examples of the negative electrode binder include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, and may also include various copolymers thereof.

[0126] The negative electrode binder may be included in an amount of 0.1 parts by weight to 50 parts by weight, based on 100 parts by weight of the negative electrode active material layer, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 10 parts by weight.

[0127] The negative electrode active material layer may not contain a conductive material, but may further contain a conductive material as necessary. The conductive material contained in the negative electrode active material layer is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives. The content of the conductive material in the negative electrode active material layer may be 0.01 to 30 parts by weight, preferably 0.03 to 25 parts by weight, based on 100 parts by weight of the negative electrode active material layer.

[0128] In one embodiment of the present application, the positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0129] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 1 μm to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0130] In one embodiment of the present application, the negative electrode may include a negative electrode current collector, and a negative electrode active material layer formed on the negative electrode current collector and including the negative electrode active material.

[0131] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has electrical conductivity. For example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the negative electrode current collector may be 1 μm to 500 μm, but the thickness of the current collector is not limited thereto.

[0132] In one embodiment of the present application, the positive electrode further includes a positive electrode active material layer containing the positive electrode active material, and the negative electrode further includes a negative electrode active material layer containing the negative electrode active material, and the thicknesses of the positive electrode and negative electrode active material layers may each be 10 μm or more and 500 μm or less. The thickness of the positive electrode active material layer may be 90% to 110%, for example 95% to 105%, of the thickness of the negative electrode active material layer, or these thicknesses may be the same. Specifically, the thicknesses of the positive electrode and negative electrode active material layers may each be 15 μm or more and 400 μm or less, 20 μm or more and 300 μm or less, 25 μm or more and 200 μm or less, or 30 μm or more and 100 μm or less.

[0133] In one embodiment of the present application, the positive electrode further comprises a positive electrode active material layer containing the positive electrode active material, and the loading amount per unit volume of the positive electrode active material layer is 250 mg / 25 cm 2 ~900mg / 25cm 2 The negative electrode further includes a negative electrode active material layer containing the negative electrode active material, and the loading amount per unit volume of the negative electrode active material layer is 100 mg / 25 cm. 2 ~600mg / 25cm 2 Specifically, the loading amount per unit volume of the positive electrode active material layer may be 270 mg / 25 cm 2 ~800mg / 25cm 2 , 285mg / 25cm 2 ~700mg / 25cm 2 , or 300 mg / 25 cm 2~600mg / 25cm 2 The loading amount per unit volume of the negative electrode active material layer may be 120 mg / 25 cm 2 ~500mg / 25cm 2 , 135mg / 25cm 2 ~400mg / 25cm 2 , or 150 mg / 25 cm 2 ~300mg / 25cm 2 may be also possible.

[0134] The positive electrode and the negative electrode may be manufactured by a conventional method for manufacturing a positive electrode and a negative electrode, except for using the positive electrode and negative electrode active materials. Specifically, the active material layer forming composition containing the active material and, optionally, a binder and a conductive material may be applied to a current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode and negative electrode active materials, the binder, and the conductive material are as described above. The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or a mixture of two or more of these may be used. The amount of the solvent used is sufficient to dissolve or disperse the active material, the conductive material, and the binder in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture the positive electrode and the negative electrode. As another method, the positive electrode and the negative electrode can also be produced by casting the active material layer forming composition on a separate support, peeling it off from the support, and laminating the resulting film on a current collector.

[0135] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.

[0136] Examples of the electrolyte include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in manufacturing lithium secondary batteries.

[0137] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0138] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0139] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte having high electrical conductivity can be prepared, and therefore such a mixture can be used even more preferably.

[0140] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0141] In addition to the constituent components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0142] The energy density of the lithium secondary battery according to one embodiment of the present application is 400Wh / L to 900Wh / L. Specifically, the energy density of the lithium secondary battery may be 425Wh / L to 875Wh / L, 450Wh / L to 850Wh / L, 475Wh / L to 825Wh / L, or 500Wh / L to 800Wh / L. When the above range is satisfied, the energy density of the lithium secondary battery designed in a limited space can be increased, the high output performance can be improved, and the cycle performance of the battery can also be improved.

[0143] The lithium secondary battery according to an embodiment of the present invention may be a cylindrical battery. The cylindrical battery may mean that the shape of the battery itself, which includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, is cylindrical, and may specifically be composed of a cylindrical can, a battery assembly provided inside the cylindrical can, and a top cap. However, the lithium secondary battery is not limited thereto, and may be a prismatic battery or a pouch battery.

[0144] A further embodiment of the present invention provides a battery module including the cylindrical battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0145] The lithium secondary battery according to the embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics, and cycle performance, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems, as well as portable devices such as mobile phones, notebook computers, and digital cameras. For example, the battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, including power tools, electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs), or power storage systems. EXAMPLES

[0146] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are merely for the purpose of illustrating the present description. It will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.

[0147] <Example 1> Based on 100 parts by weight of the positive electrode active material layer, a positive electrode active material was prepared by coating the positive electrode active material on an aluminum foil having a thickness of 103 μm, 93.3 mol % of Ni, 4.9 mol % of Co, and 1.8 mol % of Mn, and including single particles and / or similar-single particles and secondary particles (weight ratio of single particles and / or similar-single particles: secondary particles = 80:20), 1 part by weight of PVDF as a binder, and a CNT pre-dispersion liquid including 0.8 parts by weight of CNT and 0.16 parts by weight of a dispersant as a conductive material. In this case, the single particles and / or similar-single particles were prepared to a size of D50 = 3 μm by airflow pulverization, and the secondary particles were prepared to a size of D50 = 7 μm. The positive electrode active material layer was coated on an aluminum foil having a thickness of 30 μm to a thickness of 103 μm in a dry state, and then dried to prepare a positive electrode.

[0148] Based on 100 parts by weight of the negative active material layer, 97.7 parts by weight of graphite (artificial graphite: natural graphite = 70:30 weight ratio, 90 parts by weight based on 100 parts by weight of the negative active material) and silicon carbon composite (10 parts by weight based on 100 parts by weight of the negative active material) were used as the negative active material, 1.15 parts by weight of SBR (styrene-butadiene rubber) and 1 part by weight of CMC (carboxymethyl cellulose) were used as binders, and a CNT pre-dispersion liquid containing 0.09 parts by weight of a dispersant and 0.06 parts by weight of single-walled CNT was prepared. In this case, the silicon carbon composite was prepared to a size of D50 = 5 μm by airflow pulverization, and the graphite was prepared to a size of D50 = 17 μm. The composition for forming the negative active material layer was coated on a copper foil having a thickness of 15 μm so that the thickness in a dry state was 86 μm, and then dried to prepare a negative electrode.

[0149] The positive electrode and the negative electrode were stacked with a separator interposed between them, and an electrolyte (1.0M LiPF6, EC (ethylene carbonate) / EMC (ethyl methyl carbonate) = 30 / 70 (Vol%), VC (vinylene carbonate) 1.5%) was injected to prepare a battery.

[0150] <Example 2> A positive electrode was prepared in the same manner as in Example 1, except that the weight ratio of the single particle and / or the similar-single particle and secondary particle lithium composite transition metal compound was 50:50 based on 100 parts by weight of the positive electrode active material.

[0151] <Example 3> A positive electrode was prepared in the same manner as in Example 1, except that the single particles and / or similar-single particles were 100 parts by weight based on 100 parts by weight of the positive electrode active material.

[0152] <Example 4> A negative electrode was manufactured in the same manner as in Example 3, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 9 μm.

[0153] <Example 5> A negative electrode was prepared in the same manner as in Example 3, except that the amount of the silicon carbon composite was 5 parts by weight based on 100 parts by weight of the negative electrode active material.

[0154] <Example 6> A negative electrode was manufactured in the same manner as in Example 1, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 7 μm.

[0155] <Example 7> A positive electrode was manufactured in the same manner as in Example 3, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 1 μm.

[0156] <Example 8> Positive and negative electrodes were manufactured in the same manner as in Example 2, except that the D50 of the single particles and / or similar-single particles contained in the positive electrode active material layer was 1 μm, the D50 of the secondary particle-like lithium transition metal composite compound was 5 μm, and the D50 of the silicon carbon composite contained in the negative electrode active material layer was 3 μm.

[0157] <Example 9> A negative electrode was manufactured in the same manner as in Example 8, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0158] <Example 10> Positive and negative electrodes were produced in the same manner as in Example 8, except that the secondary particle-like lithium transition metal compound contained in the positive electrode active material layer had a D50 of 7 μm, and the graphite contained in the negative electrode active material layer had a D50 of 13 μm.

[0159] <Example 11> A negative electrode was manufactured in the same manner as in Example 10, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0160] <Example 12> A negative electrode was manufactured in the same manner as in Example 10, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0161] <Example 13> A positive electrode was produced in the same manner as in Example 10, except that the secondary particle-like lithium transition metal compound contained in the positive electrode active material layer had a D50 of 9 μm.

[0162] <Example 14> A negative electrode was manufactured in the same manner as in Example 13, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0163] <Example 15> A negative electrode was manufactured in the same manner as in Example 13, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0164] <Example 16> A positive electrode was produced in the same manner as in Example 8, except that the secondary particle-like lithium composite transition metal compound contained in the positive electrode active material layer had a D50 of 15 μm.

[0165] <Example 17> A negative electrode was manufactured in the same manner as in Example 10, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 5 μm.

[0166] <Example 18> A negative electrode was manufactured in the same manner as in Example 17, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0167] <Example 19> A negative electrode was manufactured in the same manner as in Example 17, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0168] <Example 20> A positive electrode was produced in the same manner as in Example 18, except that the secondary particle-like lithium transition metal compound contained in the positive electrode active material layer had a D50 of 9 μm.

[0169] <Example 21> Positive and negative electrodes were produced in the same manner as in Example 8, except that the D50 of the secondary particle-like lithium transition metal compound contained in the positive electrode active material layer was 3 μm, and the D50 of the silicon carbon composite contained in the negative electrode active material layer was 7 μm.

[0170] <Example 22> Positive and negative electrodes were produced in the same manner as in Example 21, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 9 μm.

[0171] <Example 23> Positive and negative electrodes were produced in the same manner as in Example 21, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 12 μm.

[0172] <Example 24> Positive and negative electrodes were manufactured in the same manner as in Example 10, except that the D50 of the single particles and / or similar-single particles contained in the positive electrode active material layer was 5 μm, and the D50 of the silicon carbon composite contained in the negative electrode active material layer was 7 μm.

[0173] <Example 25> A negative electrode was manufactured in the same manner as in Example 24, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0174] <Example 26> A negative electrode was manufactured in the same manner as in Example 24, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0175] <Example 27> A positive electrode was produced in the same manner as in Example 24, except that the D50 of the secondary particle-like lithium transition metal compound contained in the positive electrode active material layer was 9 μm.

[0176] <Example 28> A negative electrode was manufactured in the same manner as in Example 27, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0177] <Example 29> A negative electrode was manufactured in the same manner as in Example 27, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0178] <Example 30> A positive electrode was produced in the same manner as in Example 24, except that the secondary particle-like lithium transition metal compound contained in the positive electrode active material layer had a D50 of 15 μm.

[0179] <Example 31> A negative electrode was manufactured in the same manner as in Example 30, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0180] <Example 32> A negative electrode was manufactured in the same manner as in Example 30, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0181] <Example 33> Positive and negative electrodes were produced in the same manner as in Example 24, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 9 μm.

[0182] <Example 34> A negative electrode was manufactured in the same manner as in Example 33, except that the D50 of the graphite contained in the negative electrode active material layer was 17 μm.

[0183] <Example 35> A negative electrode was manufactured in the same manner as in Example 33, except that the D50 of the graphite contained in the negative electrode active material layer was 25 μm.

[0184] <Comparative Example 1> A positive electrode was manufactured in the same manner as in Example 1, except that the secondary particle-like lithium composite transition metal compound was 100 parts by weight based on 100 parts by weight of the positive electrode active material.

[0185] <Comparative Example 2> A positive electrode was manufactured in the same manner as in Example 3, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 0.5 μm.

[0186] <Comparative Example 3> A positive electrode was manufactured in the same manner as in Example 3, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 15 μm.

[0187] <Comparative Example 4> A negative electrode was manufactured in the same manner as in Example 3, except that the D50 of the silicon carbon composite contained in the negative electrode active material layer was 0.5 μm.

[0188] <Comparative Example 5> A negative electrode was prepared in the same manner as in Example 3, except that the amount of graphite was 100 parts by weight based on 100 parts by weight of the negative electrode active material.

[0189] <Comparative Example 6> A negative electrode was prepared in the same manner as in Example 3, except that the amount of SiO was 10 parts by weight based on 100 parts by weight of the negative electrode active material.

[0190] <Comparative Example 7> A positive electrode was manufactured in the same manner as in Example 2, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 12 μm.

[0191] <Comparative Example 8> Positive and negative electrodes were manufactured in the same manner as in Example 2, except that the D50 of the monoparticles and / or quasi-monoparticles contained in the positive electrode active material layer was 5 μm, and the D50 of the silicon carbon composite contained in the negative electrode active material layer was 3 μm.

[0192] <Comparative Example 9> A positive electrode was manufactured in the same manner as in Example 2, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 10 μm.

[0193] <Comparative Example 10> Positive and negative electrodes were manufactured in the same manner as in Example 2, except that the D50 of the single particles and / or similar-single particles contained in the positive electrode active material layer was 9 μm, the D50 of the secondary particles was 14 μm, and the D50 of the silicon carbon composite contained in the negative electrode active material layer was 7 μm.

[0194] <Comparative Example 11> A positive electrode was manufactured in the same manner as in Comparative Example 10, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 11 μm.

[0195] <Comparative Example 12> Positive and negative electrodes were manufactured in the same manner as in Comparative Example 11, except that the D50 of the monoparticles and / or quasi-monoparticles contained in the positive electrode active material layer was 10 μm, and the D50 of the silicon carbon composite contained in the negative electrode active material layer was 9 μm.

[0196] <Comparative Example 13> A positive electrode was manufactured in the same manner as in Comparative Example 12, except that the D50 of the single particles and / or quasi-single particles contained in the positive electrode active material layer was 12 μm.

[0197] <Experimental Example 1> Evaluation of energy density characteristics The energy density of the produced batteries was evaluated and is shown in Table 1 below.

[0198] The energy density of Example 1 was derived by the following calculation.

[0199] Cell volume measurement (unit: L): width (100mm) x length (300mm) x thickness (8mm) Cell energy measurement (unit: Wh): Cell capacity (40Ah) x average voltage (3.65V) Energy density measurement (unit: Wh / L): Cell energy (Wh) / cell volume (L) = 608W / L

[0200] <Experimental Example 2> Evaluation of life (capacity retention) characteristics The produced batteries were charged and discharged to evaluate their capacity retention, which is shown in Table 1 below.

[0201] The first and second cycles were charged and discharged at 0.1 C, and from the third cycle onwards, they were charged and discharged at 0.5 C. The 100th cycle ended in a charged state (with lithium in the negative electrode).

[0202] Charging conditions: CC (constant current) / CV (constant voltage) (4.25V / 0.05C current cut-off) Discharge condition: CC (constant current) condition 2.5V The capacity retention rates were calculated as follows: Capacity retention rate (%)=(100 discharge capacity / 1 discharge capacity)×100(%)

[0203] Table 1 below shows values ​​for energy density (based on Example 1, %) and capacity retention (100 cycles, %) for Examples 1 to 7 and Comparative Examples 1 to 13.

[0204] [Table 1]

[0205] Table 2 below shows the energy density (based on Example 1, %) and capacity retention (100 cycles, %) of Examples 8 to 35 based on the content of single particles and / or similar-single particles:secondary particles = 50:50 in the positive electrode and the content of silicon carbon composite:graphite = 10:90 in the negative electrode.

[0206] [Table 2]

[0207] The positive electrode active material layer according to the present invention includes single particles and / or similar-single particles having an average particle size (D50) of 1 μm or more, and the negative electrode active material layer includes a silicon carbon composite having an average particle size (D50) of more than 1 μm, and the average particle size (D50) of the single particles and / or similar-single particles is smaller than the average particle size (D50) of the silicon carbon composite. The single particles and / or similar-single particles and the silicon carbon composite have a suitable particle size distribution with an average particle size (D50), which suppresses side reactions with the electrolyte, facilitates charging and discharging, fully realizes capacity / efficiency, increases energy density, and provides stable life characteristics.

[0208] Examples 1 to 35 used positive and negative electrode active materials that satisfied the particle size range according to the present invention, and were confirmed to be excellent in energy density and capacity retention.

[0209] In contrast, Comparative Examples 1 and 5 did not contain the monoparticle and / or similar-monoparticle contained in the positive electrode active material layer of the present invention and the silicon carbon composite contained in the negative electrode active material layer, respectively, and it was confirmed that the energy density and capacity retention rate were reduced.

[0210] Comparative Example 2 does not satisfy the D50 range of the single particles and / or similar-single particles contained in the positive electrode active material layer of the present invention, and it was confirmed that the overall particle size was too small, the life performance was low, and charging and discharging was not easy, resulting in reduced capacity, efficiency, and life compared to the Examples.

[0211] In addition, in Comparative Examples 3 and 7 to 13, the D50 of the single particle and / or similar-single particle was larger than the D50 of the silicon carbon composite contained in the negative electrode active material layer, and it was confirmed that the capacity, efficiency, and lifespan were reduced.

[0212] Comparative Example 4 does not satisfy the D50 range of the silicon carbon composite contained in the anode active material layer used in the present invention, and it was confirmed that the overall particle size was too small, the life performance was low, and charging and discharging was not easy, resulting in reduced capacity, efficiency, and life compared to the Examples.

[0213] That is, in Comparative Example 4, the average particle size (D50) of the silicon carbon composite was smaller than 1 μm, the specific surface area increased, side reactions with the electrolyte occurred as the cycles progressed, and the life performance decreased. Furthermore, it was confirmed that the capacity, efficiency, and life were reduced because the D50 of the silicon carbon composite was smaller than the D50 of the single particle.

[0214] Comparative Example 6 did not contain the silicon carbon composite contained in the negative electrode active material layer used in the present invention, but contained a SiO composite, and it was confirmed that the energy density and capacity retention rate decreased.

Claims

1. A lithium secondary battery comprising: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator provided between the positive electrode and the negative electrode; and an electrolyte, The positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), The lithium composite transition metal compound includes at least one of a single particle or a similar-single particle, and at least one of the single particle or the similar-single particle has an average particle size (D50) of 1 μm or more; The monoparticulate is a complex consisting of one nodule and the pseudo-monoparticulate is a complex consisting of 30 or less nodules; The negative electrode active material includes a silicon carbon composite, and the silicon carbon composite has an average particle size (D50) of more than 1 μm; The average particle size (D50) of at least one of the monoparticulate or the quasi-monoparticulate is smaller than the average particle size (D50) of the silicon carbon composite.

2. At least one of the single particles or the quasi-single particles has an average particle size (D50) of 12 μm or less; 2. The lithium secondary battery according to claim 1, wherein the silicon carbon composite has an average particle size (D50) of less than 15 μm.

3. 2. The lithium secondary battery according to claim 1, wherein the average particle size (D50) of at least one of the single particles or the quasi-single particles is 1 μm to 12 μm smaller than the average particle size (D50) of the silicon carbon composite.

4. The lithium composite transition metal compound further includes secondary particles, 2. The lithium secondary battery according to claim 1, wherein an average particle size (D50) of at least one of the single particles or the quasi-single particles is smaller than an average particle size (D50) of the secondary particles.

5. 5. The lithium secondary battery according to claim 4, wherein the average particle size (D50) of at least one of the single particles or the quasi-single particles is 1 μm to 18 μm smaller than the average particle size (D50) of the secondary particles.

6. The negative electrode active material further includes graphite, 2. The lithium secondary battery according to claim 1, wherein an average particle size (D50) of the silicon carbon composite is smaller than an average particle size (D50) of the graphite.

7. 7. The lithium secondary battery according to claim 6, wherein the average particle size (D50) of the silicon carbon composite is 1 μm to 25 μm smaller than the average particle size (D50) of the graphite.

8. The lithium composite transition metal compound further includes secondary particles, The negative electrode active material further includes graphite, 2. The lithium secondary battery according to claim 1, wherein the average particle size (D50) of the secondary particles, at least one of the single particles or the similar-single particles, the graphite, and the silicon carbon composite is represented by A, B, C, and D, respectively, and B<D≦A<C.

9. The negative electrode active material further includes graphite, 2. The lithium secondary battery according to claim 1, wherein the average particle size (D50) of at least one of the single particle or the similar-single particle, the graphite, and the silicon carbon composite is represented by B, C, and D, respectively, and B<D<C.

10. The lithium secondary battery according to claim 1 , wherein the positive electrode active material further comprises aluminum.

11. At least one of the single particles or the similar-single particles is included in an amount of 15 parts by weight to 100 parts by weight based on 100 parts by weight of the positive electrode active material; 2. The lithium secondary battery according to claim 1, wherein the silicon carbon composite is contained in an amount of 3 parts by weight to 30 parts by weight based on 100 parts by weight of the negative electrode active material.

12. 2. The lithium secondary battery according to claim 1, wherein the lithium composite transition metal compound contains nickel in an amount of 80 mol % or more of metals other than lithium.

13. 2. The lithium secondary battery according to claim 1, wherein the positive electrode further comprises a positive electrode binder and a conductive material.

14. The lithium secondary battery according to claim 1 , wherein the lithium secondary battery is a cylindrical battery.

15. 2. The lithium secondary battery according to claim 1, wherein a ratio of an average particle size (D50) of at least one of the single particles or the quasi-single particles to an average particle size (D50) of the silicon carbon composite is 1.5:2 to 1.5:

20.

16. The positive electrode further includes a positive electrode active material layer including the positive electrode active material, and the negative electrode further includes a negative electrode active material layer including the negative electrode active material, 2. The lithium secondary battery according to claim 1, wherein the positive electrode active material layer and the negative electrode active material layer each have a thickness of 10 μm or more and 500 μm or less.

17. The positive electrode further includes a positive electrode active material layer containing the positive electrode active material, and the loading amount per unit volume of the positive electrode active material layer is 250 mg / 25 cm 2 ~900mg / 25cm 2 and The negative electrode further includes a negative electrode active material layer containing the negative electrode active material, and a loading amount per unit volume of the negative electrode active material layer is 100 mg / 25 cm 2 ~600mg / 25cm 2 The lithium secondary battery according to claim 1 ,

18. 2. The lithium secondary battery according to claim 1, wherein the energy density of the lithium secondary battery is 400 Wh / L to 900 Wh / L.

19. A battery module comprising the lithium secondary battery according to any one of claims 1 to 18.

20. A battery pack comprising the battery module according to claim 19.

Citation Information

Patent Citations

  • Secondary battery and charging method of the same

    JP2013012336A

  • Nonaqueous electrolyte secondary battery

    WO2014068931A1

  • Nonaqueous electrolyte secondary battery

    WO2021039751A1